Penerapan prinsip manajemen pendidikan Islam dalam pengembangan kurikulum sekolah Islam: menggunakan tinjauan scientific literature review - Eli Sabrifha; M. Fahli Zatrahadi; Istiqomah Istiqomah (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
Islamic education management plays an important role in the management and development of an Islamic-based curriculum. The purpose of this study was to analyze the application of Islamic education management principles in Islamic school curriculum development. The study used a systematic literature review method. The acquisition of data analyzed as many as 21 publication documents. Data obtained through database dimensions in the period 1970–2023 There were no limitations on collecting data in any form. The analysis stage uses NVivo software in order to obtain more accurate theme points. The results obtained through in vivo analysis include the formation of Islamic character, increased academic achievement, respect for Islamic values, community participation, and the application of Islamic teachings in the field. So that Islamic education can have a substantial and positive impact not only on students but also on Muslim society as a whole, maintaining and improving its quality requires the application of management principles in Islamic education.